FAKTOR YANG MEMPENGARUHI SISA MAKANAN DAN BIAYA YANG TERBUANG PADA PASIEN SKIZOFRENIA RAWAT INAP - Astri Fitriati; Reni Sofiyatin; Suhaema Suhaema; Luh Suranadi (Poltekkes Kemenkes Mataram, 2021)
Background : The success of a food maintenance system can be evaluated by observation of food waste that causes the cost to be wasted and will have an impact on the anggran used for the procurement of foodstuffs. The observations showed that in Mutiara Sukma Mental Hospital, there were still food waste that was not consumed by patients.Objective : This study aims to analyze